Changing Pattern of Characteristic Components in Black Garlic during Processing Analyzed by Ultra-high Performance Liquid Chromatography-Triple Quadrupole Tandem Mass Spectrometry - WU Peng, LIU Pingxiang, WANG Yutao, GAO Rui, JIANG Yuying, BI Jingxiu, WANG Zhengrong (Shipin Kexue, 2024)
An analytical method based on ultra-high performance liquid chromatography-triple quadrupole tandem mass spectrometry (UPLC-TQ-MS/MS) was established for the simultaneous determination of 10 flavor precursors and 21 free amino acids in black garlic. The method was applied for exploring the changing pattern of characteristic components in black garlic during processing. The results showed that the characteristic components in black garlic changed significantly during processing at 75 ℃ and 85% relative humidity. Among them, γ-aminobutyric acid, S-allyl-L-cysteine, isoalliin, glutamine, methiin, alliin, tryptophan, and γ-L-glutamyl-S-allyl-L-cysteine changed most obviously, and were identified as the chemical markers of changes in small molecular metabolites during the processing of black garlic. The established method has high sensitivity and accuracy, and can meet the detection requirements.